2019
DOI: 10.1111/odi.13044
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Porphyromonas gingivalis in gut microbiota of streptozotocin‐induced diabetic mice

Abstract: Objectives Increasing evidence suggests that periodontitis can exacerbate diabetes, and gut bacterial dysbiosis appears to be linked with the diabetic condition. The present study examined the effects of oral administration of the periodontopathic bacterium, Porphyromonas gingivalis, on the gut microbiota and systemic conditions in streptozotocin‐induced diabetic mice. Materials and Methods Diabetes was induced by streptozotocin injection in C57BL/6J male mice (STZ). STZ and wild‐type (WT) mice were orally adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 60 publications
2
42
0
Order By: Relevance
“…It has also been described in animal models of type 1 diabetes, that oral administration of P. gingivalis alters the intestinal microflora, inducing dysbiosis manifested in increased genera Brevibacterium , Corynebacterium , and Facklamia , aggravating glycemic control. In addition to the presence of microorganisms in the feces, an alteration of intestinal permeability was observed (due to action on tight intercellular junctions), as well as a dysregulation of the inflammatory response and glucose-fatty acid metabolism in the ileum and the liver ( 69 ). Thus, the translocation of oral microorganisms (including periodontopathogens) ( 69 ) and their products including citrullinated peptides in the case of P. gingivalis ( 48 ) is a recurrently cited mechanism in the interrelation between periodontal diseases, autoimmunity and other inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been described in animal models of type 1 diabetes, that oral administration of P. gingivalis alters the intestinal microflora, inducing dysbiosis manifested in increased genera Brevibacterium , Corynebacterium , and Facklamia , aggravating glycemic control. In addition to the presence of microorganisms in the feces, an alteration of intestinal permeability was observed (due to action on tight intercellular junctions), as well as a dysregulation of the inflammatory response and glucose-fatty acid metabolism in the ileum and the liver ( 69 ). Thus, the translocation of oral microorganisms (including periodontopathogens) ( 69 ) and their products including citrullinated peptides in the case of P. gingivalis ( 48 ) is a recurrently cited mechanism in the interrelation between periodontal diseases, autoimmunity and other inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…We found that oral Pg-administration upregulated hepatic gluconeogenesis-related enzymes at mRNA and protein expression levels in diabetic mice. It has already been reported that oral administration of periodontal pathogens impairs both glucose tolerance and insulin sensitivity in non-diabetic mice and in streptozotocininduced diabetic mice 13,14,18 , which are related to the increased hepatic gene expression of proin ammatory cytokines 13,18 . However, in the present study, Pg-treatment did not alter the gene expression of proin ammatory cytokines, relative to levels in the control mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…And, recent studies have shown that gut microbiota is associated with immune system diseases. For example, the development of autoimmune diseases, especially P.gingivalis [58]. Hevia et al found that the ratio of intestinal Pachymete/Bacteroides decreased in patients with systemic lupus erythematosus, indicating that mucosal immune dysfunction in patients with systemic lupus erythematosus affects intestinal microbiota [59].…”
Section: Discussionmentioning
confidence: 99%